Do Critical Reviews Affect Box Office Revenues Through Community Engagement and User Reviews? - Chiu, Ya-Ling; Du, Jiangze; Sun, Yide; Wang, Jying-Nan (Frontiers in Psychology, 2022)
With advances in technology and the popularity of the Internet, consumers increasingly rely on various sources of electronic word-of-mouth (eWOM), such as online user reviews and critical reviews, in their decision-making processes. Despite general consensus on the importance of eWOM and the ability of critical reviews to influence product sales, very little is known about the mediation between critical reviews and user reviews. Therefore, we used path analysis to examine how critical reviews and user reviews simultaneously affect box office revenues using eWOM data collected from Metacritic.com and IMDb.com, and box office revenue information collected from BoxOfficeMojo.com. The results showed that critical reviews valence not only directly affects box office revenues but also increases active postings in the community and user reviews volume, thus indirectly leading to greater box office revenues. The study provides strategic guidance and practical implications for eWOM communication management.